Syracosphaera halldalii and Calyptrolithina divergans var.tuberosa life-cycle association and relevant taxonomic remarks - Triantaphyllou, M.; Dimiza, M.; Dermitzakis, M.D. (Micropaleontology, 2004)
Water sampleswere collected for coccolithophore analysis at coastal environments, in August 2002, from 7 stations in the Gulf of Kastro (Andros Island, middle Aegean Sea, Eastern Mediterranean). The studies on coccolithophore regional dynamics in the middle Aegean Sea coastal environments have revealed a unique heterococcolith–holococcolith combination coccosphere indicating a life-cycle association of the taxa Syracosphaera halldalii in Gaarder and Hasle 1971 ex Jordan and Green 1994 and Calyptrolithina divergens var. tuberosa (Heimdal 1980) Jordan et al. 1993. Consequently their systematic taxonomy is emended and the name Syracosphaera halldalii is considered as the appropriate one for the well-established association.